2019
DOI: 10.1016/j.nmd.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic inflammatory myopathies with anti-mitochondrial antibodies: Clinical features and treatment outcomes in a Chinese cohort

Abstract: Anti-mitochondrial antibodies, the hallmark of primary biliary cirrhosis, have been detected in many patients with idiopathic inflammatory myopathies and these anti-mitochondrial-antibody-associated idiopathic inflammatory myopathies frequently show unique characteristics. We detected anti-mitochondrial antibodies in Chinese idiopathic inflammatory myopathy and summarized the clinical findings of these antimitochondrial-antibody-positive patients. Of 136 patients, seven (5.15%) were found to be anti-mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 38 publications
(72 reference statements)
8
43
1
Order By: Relevance
“…Previous studies of myositis associated with AMA have not revealed RV or other related findings. [1][2][3][4] Among idiopathic inflammatory myopathies, inclusion-body myositis commonly shows RV, but several other features in the present patient made this diagnosis less likely, including the lack of the characteristic distribution of muscle involvement (finger flexor and quadriceps muscles), no endomysial inflammatory cell infiltration surrounding or invading nonnecrotic muscle fibers, and the clearly favorable response to corticosteroid therapy. The pathogenesis of RV has been considered to be associated with the disruption of autophagy and the ubiquitin-proteasome system.…”
Section: Jcnmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous studies of myositis associated with AMA have not revealed RV or other related findings. [1][2][3][4] Among idiopathic inflammatory myopathies, inclusion-body myositis commonly shows RV, but several other features in the present patient made this diagnosis less likely, including the lack of the characteristic distribution of muscle involvement (finger flexor and quadriceps muscles), no endomysial inflammatory cell infiltration surrounding or invading nonnecrotic muscle fibers, and the clearly favorable response to corticosteroid therapy. The pathogenesis of RV has been considered to be associated with the disruption of autophagy and the ubiquitin-proteasome system.…”
Section: Jcnmentioning
confidence: 73%
“…Myositis associated with antimitochondrial antibodies (AMAs) is characterized by proximal and axial muscle weakness and cardiac involvement. 1 2 3 4 The muscle pathology most commonly manifests as necrotizing myopathy with a variable extent of inflammatory cell infiltrates. Granulomatous inflammation has been observed in 25% of myositis patients.…”
mentioning
confidence: 99%
“…We therefore measured the antibodies against SRP and HMGCR, and the results were negative. In addition, anti-mitochondrial M2 and anti-ARS antibodies, which are associated with IMNM (11,12), were also negative. Therefore, we considered the case to be one of seronegative immune-mediated necrotizing myopathy.…”
Section: Discussionmentioning
confidence: 99%
“…1 The frequency of AMA-positive Cardiac involvement with AMA-positive myositis myositis in idiopathic inflammatory myopathies is reported to vary depending on the country: Japan (11.3-19.5%), France (7.8%), China (5.15%), and North America (0.6%). 1,2,5,6 AMA-positive myositis is characterized by chronic progressive respiratory muscle weakness, muscular atrophy, and cardiac involvement. 1 Among these patients, 20-30% have cardiac involvement including arrhythmias and LV dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…AMA is most commonly found in association with primary biliary cirrhosis 6 ; however, it has also been linked to idiopathic inflammatory myopathies 1 . The frequency of AMA‐positive myositis in idiopathic inflammatory myopathies is reported to vary depending on the country: Japan (11.3–19.5%), France (7.8%), China (5.15%), and North America (0.6%) 1,2,5,6 . AMA‐positive myositis is characterized by chronic progressive respiratory muscle weakness, muscular atrophy, and cardiac involvement 1 .…”
Section: Discussionmentioning
confidence: 99%